Crime of imitating the registered trade mark: comparative analytical study - AL HILAI , A.J.S. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The subject of the crime of imitating the registered trademark is considered one of the most important and vital issues because it relates to the consumer and countries’ economy. Its development on the one hand, and the increasing role of the trademark in distinguishing goods and services for other goods and services similar to them and preventing theft on the other, as international interest in intellectual property and its elements, especially trademarks, has increased. It should be noted that the trademarks are subject to many assaults especially the imitating, which is not limited to local brands but also includes foreign marks. RESUMEN El tema del delito de imitación de la marca registrada se considera una de las cuestiones importantes y vitales porque se relaciona con el consumidor y la economía de los países y su desarrollo, por un lado, y el papel cada vez más importante de la marca en la distinción de productos y servicios para otros bienes y servicios similares a ellos y la prevención del robo por otro, ya que el interés internacional en la propiedad intelectual y sus elementos, especialmente las marcas, han aumentado en los últimos tiempos. Estas últimas, están sujetas a muchos ataques, especialmente la imitación que no se limita a las marcas locales.